(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The article discusses the problem of the defeat of the grapevine by a widespread disease - an mildew and oidium disease/ as measures to combat this disease, the use of fungicide vi starstop 32.5% c.c. is recommended with a flow rate of 0.5 l/ha. Before the experiment, the leaves were affected by an average of 9.6-9.8%. the biological efficacy of suppressing the disease on leaves on day 88.8-87.8%, on day 88.2- 89.5%, then on day 45 decreased to 88.4-88.9%.